2018
DOI: 10.1016/j.rse.2018.04.013
|View full text |Cite
|
Sign up to set email alerts
|

Retrieving surface soil moisture at high spatio-temporal resolution from a synergy between Sentinel-1 radar and Landsat thermal data: A study case over bare soil

Abstract: Radar data have been used to retrieve and monitor the surface soil moisture (SM) changes in various conditions. However, the calibration of radar models whether empirically or physically-based, is still subject to large uncertainties especially at high-spatial resolution. To help calibrate radar-based retrieval approaches to supervising SM at high resolution, this paper presents an innovative synergistic method combining Sentinel-1 (S1) microwave and Landsat-7/8 (L7/8) thermal data. First, the S1 backscatter c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
92
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

4
5

Authors

Journals

citations
Cited by 135 publications
(96 citation statements)
references
References 115 publications
4
92
0
Order By: Relevance
“…In this study, we use both Sentinel-1A and Sentinel-1B backscatter data, with a resolution of 10 m and a temporal resolution of 12 days, for each satellite. Previous studies have shown that VV (vertical-vertical) polarization data, in comparison to VH (vertical-horizontal) polarization, show high sensitivity to soil moisture [37][38][39][40][41][42]. VH data, in its turn, has a higher sensitivity to volume scattering, which depends strongly on the geometrical alignment and characteristics of the vegetation.…”
Section: Sentinel-1 Datamentioning
confidence: 99%
“…In this study, we use both Sentinel-1A and Sentinel-1B backscatter data, with a resolution of 10 m and a temporal resolution of 12 days, for each satellite. Previous studies have shown that VV (vertical-vertical) polarization data, in comparison to VH (vertical-horizontal) polarization, show high sensitivity to soil moisture [37][38][39][40][41][42]. VH data, in its turn, has a higher sensitivity to volume scattering, which depends strongly on the geometrical alignment and characteristics of the vegetation.…”
Section: Sentinel-1 Datamentioning
confidence: 99%
“…Direct scattering from the canopy and the soil, as well as multiple interactions between vegetation components and the background soil, contributes to the scattering characteristics of the SAR response [26]. Thus, eliminating the vegetation and surface roughness contributions to the SAR backscattering is essential for accurately retrieving SSM over agricultural fields during the growing season [27], which requires the determination of soil surface roughness [28] and canopy properties [28,29]. The parameterization of surface roughness and its spatial variability can pose major challenges for SSM retrieval [30].…”
mentioning
confidence: 99%
“…For thermal data, land surface temperature (LST) derived from thermal infrared remote sensing data have been used in a variety of applications such as, among others, climate studies [62,63], the monitoring of crop water consumption and water stress detection [64][65][66][67], vegetation monitoring [68,69], soil moisture estimation [70][71][72]. Canopy temperature has long been recognized as a good indicator for crop water status and as a potential tool for irrigation scheduling.…”
Section: Remote Sensingmentioning
confidence: 99%
“…Especially, the Sentinel-1 (S1) constellation (composed of two satellites S1-A and S1-B) potentially provides SAR data at 20 m resolution every 3 days [74]. Thus, numerous studies have investigated and exploited the sensitivity of the radar signal to SM [70,[75][76][77][78][79][80].…”
Section: Remote Sensingmentioning
confidence: 99%